Thiamine-Reduced Fatigue in Quiescent Inflammatory Bowel Disease Is Linked to Faecalibacterium prausnitzii Abundance - Sandra Bermúdez-Sánchez; Palle Bager; Jens Frederik Dahlerup; Simon Mark Dahl Baunwall; Tine Rask Licht; Martin Steen Mortensen; Christian Lodberg Hvas (Gastro Hep Advances)
Background and Aims: Chronic fatigue is common in patients with inflammatory bowel disease (IBD). The gut microbiota, specifically, microbial diversity and butyrate-producing bacteria have been linked to the fatigue pathogenesis. High-dose oral thiamine reduces fatigue, potentially through gut microbiota modification. In this study, we investigated how the gut microbiota influences the efficacy of high-dose thiamine in alleviating chronic fatigue in quiescent IBD (qIBD). Methods: We analyzed the microbiota and short-chain fatty acids concentrations in fecal samples from patients with qIBD, with (n = 40) or without (n = 20) chronic fatigue. The 40 patients with qIBD and fatigue were included in a randomized, placebo-controlled, crossover trial to assess a 4-week high-oral-dose thiamine regimen. Results: Butyrate and butyrate-producing bacteria were similar in patients with and without fatigue and did not change with high-dose thiamine treatment. Notably, Faecalibacterium prausnitzii was more abundant in thiamine responders compared with nonresponders both pretreatment (P = .019) and post-treatment (P = .038). The relative abundances of Faecalibacterium prausnitzii and Roseburia hominis, both pretreatment and post-treatment, inversely correlated with IBD fatigue score changes for patients with chronic fatigue (PRE; R = −0.48, P = .004, and R = −0.40, P = .018; POST; R = −0.42, P = .012, and R = −0.40, P = .017) respectively. Conclusion: Faecalibacterium prausnitzii and Roseburia hominis may serve as markers for response to high-dose thiamine in alleviating chronic fatigue in patients with qIBD. The mechanistic role of gut bacteria and butyrate in patients with chronic fatigue and qIBD should be further explored.